2013
DOI: 10.2215/cjn.02790313
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Complement Pathway Activation Products in Urine and Kidneys of Patients with ANCA-Associated GN

Abstract: SummaryBackground and objectives Previous study revealed that complement activation products of the alternative pathway could be detected in renal specimens of human ANCA-associated vasculitis. The current study aimed to investigate the clinical and pathologic significance of complement activation products in the urine and kidneys of patients with ANCA-associated vasculitis.Design, setting, participants, & measurements Renal biopsy specimens from 29 patients with ANCA-associated vasculitis diagnosed at Peking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
100
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(110 citation statements)
references
References 29 publications
6
100
0
1
Order By: Relevance
“…The complement activation products were detected in kidneys of patients with AAV, even in ANCAnegative AAV patients [4][5][6][7]22]. The complement system was regulated strictly in the normal state.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The complement activation products were detected in kidneys of patients with AAV, even in ANCAnegative AAV patients [4][5][6][7]22]. The complement system was regulated strictly in the normal state.…”
Section: Discussionmentioning
confidence: 97%
“…Considerable evidence has confirmed that activation of the complement system is involved in the pathogenesis of AAV [7,20,21]. The complement activation products were detected in kidneys of patients with AAV, even in ANCAnegative AAV patients [4][5][6][7]22].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The mouse model of anti-MPO IgG-induced NCGN identified an unsuspected role of complement activation [53] that has subsequently been supported by observations in patients [54,55,56,57,58,59]. The NCGN induced by transfer of anti-MPO IgG into wild-type mice or anti-MPO splenocytes into immunodeficient (Rag2-/-) mice could be completely blocked by complement depletion using cobra venom factor [53].…”
Section: Complement In Anca Pathogenesismentioning
confidence: 99%